Highlights from the 7th Cachexia Conference: muscle wasting pathophysiological detection and novel treatment strategies. Issue 1 (5th March 2014) - Ebner, Nicole; Steinbeck, Lisa; Doehner, Wolfram; Anker, Stefan D.; von Haehling, Stephan
Abstract : This article highlights preclinical and clinical studies in the field of wasting disorders that were presented at the 7th Cachexia Conference held in Kobe, Japan, in December 2013. This year, the main topics were the development of new methods and new biomarkers in the field of cachexia and wasting disorders with particular focus on inflammatory pathways, growth differentiation factor‐15, myostatin, the ubiquitin proteasome‐dependent pathway, valosin and the regulation of ubiquitin‐specific protease 19 that is involved in the differentiation of myogenin and myosin heavy chain. This article presents highlights from the development of drugs that have shown potential in the treatment of wasting disorders, particularly the ghrelin receptor agonist anamorelin, the myostatin antagonist REGN1033, the selective androgen receptor modulators enobosarm and TEI‐E0001, and the anabolic catabolic transforming agent espindolol. In addition, novel data on the prevalence and detection methods of muscle wasting/sarcopenia are presented, including the D3‐creatine dilution method and several new biomarkers.